Levels of Madrasati (M) LMS utilization among teachers - Alharbi, Hamad Muaybid; Ab Jalil, Habibah; Omar, Muhd Khaizer; Mohd Puad, Mohd Hazwan (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2023)
Performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), attitudes, competence, and behavioral intention are all linked to poor Madrasati (M) utilization and acceptance among teachers. This study aims to examine the extent to which teachers are using M LMS. The impact of these parameters on M LMS usage was quantified using a survey method. Out of the 13,782 people, 374 teachers who use Madrasati in public schools were sampled. This study revealed that levels of M LMS utilization among teachers in schools were significantly affected by PE, EE, SI, FC, competence to use M, and behavioral intention factors. However, teachers’ attitudes have an insignificant effect on M LMS utilization. This finding suggests that the success of M utilization in public schools is not dependent on the attitudes of teachers toward its use. This study examined factors influencing the extent of Madrasati adoption and utilization among teachers.